2009
DOI: 10.1007/s12265-009-9161-2
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning and Stem Cell Survival

Abstract: The harsh ischemic and cytokine-rich microenvironment in the infarcted myocardium, infiltrated by the inflammatory and immune cells, offers a significant challenge to the transplanted donor stem cells. Massive cell death occurs during transplantation as well as following engraftment which significantly lowers the effectiveness of the heart cell therapy. Various approaches have been adopted to overcome this problem nevertheless with multiple limitations with each of these current approaches. Cellular preconditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 128 publications
3
92
0
2
Order By: Relevance
“…Previous studies have explored different strategies to enhance the survival rate of the donor cells using growth factor genes24 or preconditioning donor stem cells with different interventions including nitric oxide donor,25 HO‐1 inducer CoPP26 and exposure to hypoxia 27, 28. Our recent report10 and the present study demonstrated that the endogenous peptide bradykinin can initiate proliferation and migration of human cardiac c‐Kit + progenitor cells.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have explored different strategies to enhance the survival rate of the donor cells using growth factor genes24 or preconditioning donor stem cells with different interventions including nitric oxide donor,25 HO‐1 inducer CoPP26 and exposure to hypoxia 27, 28. Our recent report10 and the present study demonstrated that the endogenous peptide bradykinin can initiate proliferation and migration of human cardiac c‐Kit + progenitor cells.…”
Section: Discussionsupporting
confidence: 50%
“…Pharmacological pretreatment has been shown to be a rational approach to reinforce the cells to withstand the ischemic and reperfusion injury environment. 5) Tetramethylpyrazine (TMP), a biologically active alkaloid extracted from Ligusticum chuanxiong HORT (Umbelliferae), has been widely used in China for the treatment of cardiovascular and cerebrovascular diseases. 6) Its effects are mainly related to its antioxidative, anti-apoptosis, and anti-inflammatory actions.…”
mentioning
confidence: 99%
“…Massive cell death thus occurs during transplantation and following engraftment, which significantly lowers the effectiveness of the clinical therapy. The simulated hypoxia microenvironment triggers the improved survival of the SCs in vitro and after transplantation [62,64]. Studies show that sub-lethal levels of hypoxia can significantly increase the tolerance of treated cells to apoptotic and other insults in vitro as well as in the harsh environments of the ischemic and adjacent regions.…”
Section: Enhanced Cell Survivalmentioning
confidence: 99%